Status of contact screening and isoniazid preventive therapy for children under age six in Puducherry district, under the Revised National Tuberculosis Control Programme: An operational research - Ariarathinam Newtonraj (Journal of Current Research in Scientific Medicine, 2020)
Introduction: We assessed the contact screening of smear-positive pulmonary tuberculosis (PTB) and the coverage of isoniazid preventive therapy (IPT) in Puducherry district of Puducherry State. Methods: A retrospective record review of treatment cards, under the Revised National Tuberculosis Control Programme, was conducted between the reference period of October 2018 and December 2018. Results: A total of 145 index cases were linelisted. Among them, the number of household contacts of >6 years was 399, of which 359 (90%) were screened for PTB and one was diagnosed with PTB and initiated on treatment. Among the 35 children<6 years, 31 (89%) were screened and none was found to be positive for PTB. All patients were put on treatment (89%), of which 25 (71%) completed 6 months of IPT. Conclusions: Implementation of IPT in Puducherry district was satisfactory, and still, there is a hope to improve further. Nationwide data on contact screening and IPT implementation are required.